The response of inclusive schools to the needs of children exposed to Adverse Childhood Experiences - Corres-Medrano, Irune; Smith-Etxeberria, Klara; Fernández-Villanueva, Itziar (Frontiers in Psychology, 2025)
This research seeks to explore the bidirectional adaptation of the educational community in schools that take in children at risk and who have suffered ACE. On the one hand, it describes the psychological adjustment of children at risk to the school context. On the other hand, it reports on the school's response to the needs of these children. Three public primary schools characterized by social and school segregation participated in this study. Participants included 25 primary education professionals and 144 third- and fourth-year primary school children, from diverse cultural backgrounds. Data collection techniques consisted of participant observation, semi-structured interviews and focus groups. The analysis revealed the following five themes: (1) emotional instability of students; (2) the crisis of authority questions the place of the teacher; (3) difficulties in good teaching practices; (4) grouping and segregation of students; and (5) need for other material and human resources on the part of teachers. Findings suggest the need to develop comprehensive and systemic lines of research and intervention that take into account both the individual characteristics of children and the social factors that characterize schools. In addition, the fundamental role played by inclusive schools in addressing the rights of these most vulnerable children and ensuring their well-being is highlighted.